FENOMENA TABARRUJ DI ERA DIGITAL DALAM PERSPEKTIF AL-QURAN - Muhammad Ihsan; Kharis Nugroho (AL-BAYAN INSTITUTE, 2024)
The development of digital communication technology has created a new lifestyle that significantly influences how Muslim women express themselves in public spaces, particularly through sosial media platforms such as TikTok, Instagram, and Facebook. This phenomenon has led to the rise of tabarruj (a practice of excessive beautification and self-exposure intended to attract male attention) which is clearly prohibited in Islamic teachings. This study aims to explore the transformation of the concept of tabarruj within the Qur’anic perspective, through the interpretations of both classical and contemporary Islamic scholars. It also investigates how tabarruj manifests in various forms on sosial media today. The study employs a literature review and ethnographic content analysis. Five major Qur’anic exegeses are examined: Tafsir Al-Jami’ li Ahkam al-Qur’an (Imam Al-Qurthubi), Tafsir Al-Thabari, Tafsir Al-Munir (Wahbah az-Zuhaili), Tafsir Al-Azhar (Buya Hamka), and Tafsir Al-Mishbah (Quraish Shihab). Findings show a unanimous agreement among scholars that tabarruj is forbidden, though their interpretations vary based on historical and cultural contexts. In the digital age, tabarruj transcends physical presence and is often displayed in online content such as dancing videos, tight or extravagant clothing, excessive makeup, fashion content (OOTD, GRWM), and even the overuse of the niqab (face veil) not as a sign of piety, but as a tool for gaining popularity or aesthetic appeal. This research highlights how sosial media has become a powerful space for tabarruj, potentially undermining the ethical values and dignity of Muslim women in modern society.